Principals’ Toxic Leadership Behaviour and Teachers’ Workplace Incivility in Public Senior Secondary Schools, Lagos State, Nigeria - Nurudeen Olalekan Orunbon; Ganiyu Abiona Ibikunle (PT ARRUS Intelektual Indonesia, 2023)
This paper examines the connection between toxic leadership and workplace incivility among teachers in the selected public senior secondary schools in Lagos, Nigeria. Using the stratified sampling technique, 1,274 respondents consisting of 98 principals, 196 vice-principals, and 980 teachers were selected from a total population of 20,243. A structured questionnaire was used to collect quantitative data. The Statistical Package for Social Science (SPSS) version 24.0 was used to analyse quantitative data, and the Pearson’s Product-Moment Correlation was used to test the hypotheses with the results shows that toxic leadership behaviour had a negative and non-significant correlation with teachers’ hostility in Lagos State senior secondary (r = -0.029, >0.05), and toxic leadership behaviour showed no significant correlation with teachers' withdrawal behaviour (r = 0.025, >0.05). The paper concludes that toxic leadership accounts for the derogatory treatment meted on teachers at work on Lagos State’s public senior secondary schools; and recommend the need for the Lagos State Education Districts to replace toxic leaders in schools with contemporary leadership styles that encourage team work and collaboration among teachers and allow participation in the process of decision-making.